Polystyrene nanoplastics promote the blood-brain barrier dysfunction through autophagy pathway and excessive erythrophagocytosis - Eun-Hye Kim; Seung Mi Baek; Han Jin Park; Yiying Bian; Han Young Chung; Ok-Nam Bae (Ecotoxicology and Environmental Safety)
There is increasing concern regarding the risks posed by plastics to human health. Nano-sized plastics enter the body through various exposure routes. Although nano-sized particles circulate through the bloodstream and access the blood-brain barrier (BBB), the harmful impacts of nano-sized plastics on BBB function including endothelial cells are not well known. In this study, polystyrene nanoplastics (PS-NP) resulted in hyperpermeability and damaged tight junction proteins in brain endothelial cells. We identified that PS-NP increased intracellular iron levels by inhibiting the autophagy pathway in brain endothelial cells. Our study showed that dysregulated autophagy pathways led to increased BBB permeability induced by PS-NP treatment. In addition, PS-NP caused excessive erythrophagocytosis in brain endothelial cells via damaged red blood cells. PS-NP-treated RBCs (NP-RBC) induced the BBB dysfunction and increased intracellular iron levels and ferroptosis in brain endothelial cells. We provide novel insights into the potential risks of nano-sized plastics in BBB function by interaction between cells as well as direct exposure. Our study will help to understand the cardiovascular toxicity of nano-sized plastics.